Treatment Of The Dısturbed Eruptıon Of Mandıbular Permanent Fırst And Second Molars (Report Of Two Cases) - İlken Kocadereli; Hakan El (Galenos Yayinevi, 2003)
The case reports presented the irreversible disturbed eruption of mandibular permanent first and second molars. Using specially designed lingual arch, the ectopic eruption of mandibular permanent first and second molars has been successfully uprighted and retained.